The power of vivid experience in hand hygiene compliance - Nicol, Paul; Watkins, Rochelle; Donovan, Robert; Wynaden, Dianne; Cadwallader, H (Elsevier, 2009)
Summary In recent years, explicit behavioural theories have been used insome research into hand hygiene behaviour. One of the most prominent ofthese has been the theory of planned behaviour (TPB). In this qualitativestudy aimed at increasing understanding of infection prevention practicein the acute care setting, TPB was identified as a suitable framework forthe emergence of new insights that have the potential to improve thepower of existing education and training. The theory emerging from the researchwas based on a finding that individual experience is of greater importthan formal education in explaining hand hygiene behaviour. Thisindicated that exposure to vivid vicarious experience is a potential meansto improving the power of existing training methods and increasing the propensityfor instilling sustainable adequate hand hygiene habits.